2019
DOI: 10.1037/edu0000292
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and empathy in aggressors and victims of school violence.

Abstract: The present study was organized around 2 main objectives: first, to analyze emotional intelligence (EI) both in aggressors and victims of school violence, considering 3 dimensions of EI—emotional attention, emotional clarity, and emotion regulation—and second, to analyze empathy in aggressors and victims of school violence, taking into consideration 2 dimensions—cognitive and affective empathy. Participants were 1,318 Spanish adolescents, aged between 11 and 17 years (47% boys) enrolled in 4 secondary schools,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 52 publications
3
34
0
6
Order By: Relevance
“…There is a paucity of studies examining the association between suicide and EI in adolescence (Domínguez-García & Fernández-Berrocal, 2018), and even less in contexts of traditional bullying and cyberbullying. However, some findings (e.g., Baroncelli Estévez et al, 2019;Extremera et al, 2018;Quintana-Orts et al, 2019) have suggested that EI may be an important protective factor against the detrimental effects of bullying and cyberbullying victimisation, by promoting more positive ways of coping with stressful situations.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of studies examining the association between suicide and EI in adolescence (Domínguez-García & Fernández-Berrocal, 2018), and even less in contexts of traditional bullying and cyberbullying. However, some findings (e.g., Baroncelli Estévez et al, 2019;Extremera et al, 2018;Quintana-Orts et al, 2019) have suggested that EI may be an important protective factor against the detrimental effects of bullying and cyberbullying victimisation, by promoting more positive ways of coping with stressful situations.…”
Section: Article In Pressmentioning
confidence: 99%
“…Recent research using adolescent participants (Estévez et al, 2019;Gomez-Baya et al, 2017;Martins et al, 2010) has found that individuals high in EI are more likely to deal appropriately with negative events than their lower-EI peers. Such effects have been attributed to this group's superior affective perceptions which, in turn, reduce the risk of negative mood states and emotional problems.…”
Section: Article In Pressmentioning
confidence: 99%
“…Deficits in EI or its dimension have been positively related to cybervictimization [ 24 ], as recently indicated by Elipe et al [ 25 ], who found that, when taking into account the dimensions of EI, cybervictims have greater competence in attending to their emotions, but lower competence in understanding and regulating them [ 25 , 38 , 39 ]. These results suggest the important role that the emotion regulation dimension plays in cybervictims.…”
Section: Introductionmentioning
confidence: 98%
“…An emotional quotient also contributes to someone's aggressive behavior. Many studies conclude that emotional quotient significantly affects students' aggressive behavior [11], [12].…”
Section: Introductionmentioning
confidence: 99%